The Effects of Bacterial Inoculants on the Fermentation, Aerobic Stability and Feed Value of Rye (Secale cereale L.) Silages - Serkan Uğurlu; Berrin Okuyucu; Mehmet Levent Özdüven (Turkish Journal of Agriculture: Food Science and Technology, 2022)
This study was carried out to determine the effects of lactic acid bacteria (LAB) inoculants and lactic acid bacteria+enzymes (LAB+E) inoculant on the fermentation, aerobic stability, and feed value of rye silages. Whole crop rye was harvested at dough stage. Biosil (Wuthenow, Germany), Silaprilis Pro (Timac Agro, USA) and Sil-All (Allteck, UK) were used as lactic acid bacteria and lactic acid bacteria+enzyme mixture inoculants. Inoculants were applied to silages at 6.00 log10 cfu/g levels. After the treatment, alfalfa was ensiled in 1.0-L special polyethylene vacuum bags. The bags were stored at 20±2°C under the laboratory conditions. Three bags from each group were sampled for chemical and microbiological analyses 2, 4, 8 and 75th days after ensiling. At the end of the ensiling period, all silages were subjected to an aerobic stability test for 5 days. In addition, in vitro dry matter, and organic matter digestibility of experiment silages were determined. The results showed that lactic acid bacteria and lactic acid bacteria+enzyme mixture inoculants increased characteristics of fermentation and aerobic stability of rye silages. Lactic acid bacteria+enzyme mixture inoculants decreased neutral detergent fiber, acid detergent fiber and celluloses content in the silages. Lactic acid bacteria+enzyme mixture inoculants increased in vitro dry matter digestibility, organic matter digestibility and metaboze energy of rye silages. Therefore, lactic acid bacteria and lactic acid bacteria+enzyme mixture inoculants might improve the fermentation properties and feed values of rye silages harvested at dough stage.